The black mass [videorecording (DVD)] - Pinn, Devanny; Pinn, Devanny; Slagle, Brandon; Pereira, Eric; Romano, Michelle; Sykes, Andrew; Hamilton, Eva; Nicklin, Sarah; Gilson, Chelsea; Kinmont, Kathleen; London, Jeremy, 1972-; Lanier, Susan, 1947-; et al. (Cleopatra Entertainment, 2024)
Inspired by real events, this film is set over a 24-hour period in Florida during the winter of 1978 when a serial killer was stalking college girls.